Sosialisasi Penggunaan Gadget dan Literasi Baca Tulis Sebagai Upaya Peningkatan Minat Baca-Tulis Peserta Didik - Indah Nurmahanani; Erna Suwangsih; Mifta Aulia Fitriyani; Cintia Marsela; Erta Alvani; Liana Wahyuningsih (Jurnal Informasi Pengabdian Masyarakat, 2023)
P3K UPI Purwakarta students carried out this socialization activity at one of the elementary schools in purwakarta. This activity was carried out to educate students about the literacy skills of reading and writing of students coupled with the use of gadgets in everyday life. Based on observations, it is known that students are more interested in using their gadgets to browse social media than reading or writing, which is one of the factors that cause students' reading and writing literacy to be low. This socialization can provide additional information for students and also foster awareness in students to read or write and can use gadgets according to their uses to help students improve their literacy skills.